Fibrates ameliorate the course of bacterial sepsis by promoting neutrophil recruitment via CXCR2. Issue 6 (22nd April 2014) - Tancevski, Ivan; Nairz, Manfred; Duwensee, Kristina; Auer, Kristina; Schroll, Andrea; Heim, Christiane; Feistritzer, Clemens; Hoefer, Julia; Gerner, Romana R; Moschen, Alexander R; Heller, Ingrid; Pallweber, Petra; et al.
Abstract Bacterial sepsis results in high mortality rates, and new therapeutics to control infection are urgently needed. Here, we investigate the therapeutic potential of fibrates in the treatment of bacterial sepsis and examine their effects on innate immunity. Fibrates significantly improved the survival from sepsis in mice infected with Salmonella typhimurium, which was paralleled by markedly increased neutrophil influx to the site of infection resulting in rapid clearance of invading bacteria. As a consequence of fibrate‐mediated early control of infection, the systemic inflammatory response was repressed in fibrate‐treated mice. Mechanistically, we found that fibrates preserve chemotaxis of murine neutrophils by blocking LPS‐induced phosphorylation of ERK. This results in a decrease of G protein‐coupled receptor kinase‐2 expression, thereby inhibiting the LPS‐mediated downregulation of CXCR2, a chemokine receptor critical for neutrophil recruitment. Accordingly, application of a synthetic CXCR2 inhibitor completely abrogated the protective effects of fibrates in septicemia in vivo. Our results unravel a novel function of fibrates in innate immunity and host response to infection and suggest fibrates as a promising adjunct therapy in bacterial sepsis.